Containers in OpenStack : leverage OpenStack services to make the most of Docker, Kubernetes and Mesos /: leverage OpenStack services to make the most of Docker, Kubernetes and Mesos. (2017) - Singh, Pradeep Kumar; Kumari, Madhuri
No abstract available